Deconstructing sociality: the types of social connections that predict longevity in a group-living primate. Issue 1917 (11th December 2019) - Ellis, Samuel; Snyder-Mackler, Noah; Ruiz-Lambides, Angelina; Platt, Michael L.; Brent, Lauren J. N.
Abstract : Many species use social interactions to cope with challenges in their environment and a growing number of studies show that individuals which are well-connected to their group have higher fitness than socially isolated individuals. However, there are many ways to be 'well-connected' and it is unclear which aspects of sociality drive fitness benefits. Being well-connected can be conceptualized in four main ways: individuals can be socially integrated by engaging in a high rate of social behaviour or having many partners; they can have strong and stable connections to favoured partners; they can indirectly connect to the broader group structure; or directly engage in a high rate of beneficial behaviours, such as grooming. In this study, we use survival models and long-term data in adult female rhesus macaques ( Macaca mulatta ) to compare the fitness outcomes of multiple measures of social connectedness. Females that maintained strong connections to favoured partners had the highest relative survival probability, as did females well-integrated owing to forming many weak connections. We found no survival benefits to being structurally well-connected or engaging in high rates of grooming. Being well-connected to favoured partners could provide fitness benefits by, for example, increasing the efficacy of coordinated or mutualistic behaviours.